A Khmer Temple on Khon Island in South Laos: Evidence of a lost quincunx at the Mekong cataract waterfall? Some considerations on the pañcāyatana complexes in Khmer architecture - Gabel, Joachim (Journal of Global Archaeology, 2023)
The remains of a small Khmer temple hidden within the compound of Wat Ban Khon Tai on Don Khon in South Laos were thoroughly investigated. Although these remains are in a poor state of preservation, the archaeological evaluation together with the special geographical situation at the Mekong cataract waterfall could indicate the former existence of a multi-towered temple or even a quincunx. The true quincunx is an exception in Khmer architecture and was essentially reserved for a small number of large monuments at Angkor. Beyond Angkor it occurs only at a few other sites of the Khmer empire but of more modest dimensions. The arrangement of five towers mirrors not only the Indian cosmogony focused on Mount Meru but also the pañcāyatana concept. Together with the stepped pyramid of indigenous origin the Khmer finally created an amalgam of Indian and local architectural perceptions culminating in the state temple-mountains of Angkor.